1991
DOI: 10.1021/bi00223a015
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate structures of recombinant soluble human CD4 expressed in Chinese hamster ovary cells

Abstract: Infection of T-lymphocytes and macrophages by human immunodeficiency virus (HIV) is mediated by the binding of the HIV envelope glycoprotein to the cell-surface receptor glycoprotein CD4. A soluble, recombinant CD4 molecule (rCD4), produced by expression of a truncated CD4 gene in Chinese hamster ovary (CHO) cells [Smith et al. (1987) Science 238, 1704-1707], is in clinical trials as a potential therapeutic agent in the treatment of acquired immunodeficiency syndrome (AIDS). In the present study, the structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
53
0
3

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 35 publications
6
53
0
3
Order By: Relevance
“…The mass accuracy for the smallest signal labeled, Hyb 4, is better than 0.05%. This mass accuracy combined with previously obtained oligosaccharide structural information is sufficient to infer the structures shown in Table II and III (Spellman et al, 1989). All structures reported by Spellman et al (1989) are observed in the two mass spectra (Figures 4 and 5).…”
Section: Comparison Of the 96-well Methods To The Standard Solution Mementioning
confidence: 56%
See 3 more Smart Citations
“…The mass accuracy for the smallest signal labeled, Hyb 4, is better than 0.05%. This mass accuracy combined with previously obtained oligosaccharide structural information is sufficient to infer the structures shown in Table II and III (Spellman et al, 1989). All structures reported by Spellman et al (1989) are observed in the two mass spectra (Figures 4 and 5).…”
Section: Comparison Of the 96-well Methods To The Standard Solution Mementioning
confidence: 56%
“…This mass accuracy combined with previously obtained oligosaccharide structural information is sufficient to infer the structures shown in Table II and III (Spellman et al, 1989). All structures reported by Spellman et al (1989) are observed in the two mass spectra (Figures 4 and 5). No ions corresponding to losses of H 2 O are observed in Figure 4 indicating that lactone formation of sialylated oligosaccharides does not occur during isolation.…”
Section: Comparison Of the 96-well Methods To The Standard Solution Mementioning
confidence: 56%
See 2 more Smart Citations
“…A d 8 4 is only partially glycosylated leading to glycoprotein variants with two or three oligosaccharide chains. Carbohydrate structure analyses of tPA from Bowes melanoma cells (Pohl et al, 1987;Parekh et al, 1989a;Chan et al, 1991) or human colon fibroblasts (Parekh et al, 1989a) as well as recombinant tPA from Chinese hamster ovary cells (Spellman et al, 1989;Chan et al, 1991) or C127 cells (Pfeiffer et al, 1989) demonstrated a site-specific glycosylation of this enzyme in so far as Asnll7 carries almost exclusively high-mannosetype glycans, whereas Asnl84 and Asn448 bear preponderantly complex-type sugar chains. Furthermore, melanomaderived tPA as well as recombinant tPA expressed in Chinese hamster ovary or human embryonic kidney cells were found to carry an O-glycosidically linked fucose residue in their domain which resembles epidermal-growth-factor (EGF) (Harris et al, 1991).…”
mentioning
confidence: 99%